Three-year-cohort-study: clinical and cost effectiveness of an inpatient psychiatric rehabilitation - Awara, Mahmoud A.; Downing, Laura M.; Edem, Dorothy; Lewis, Norma; Green, Joshua T. (Frontiers in Psychiatry, 2023)
Introduction There has been a resurgence of interest in psychiatric rehabilitation to cater to patients with chronic and complex mental illnesses. Aims This study is aimed at examining patients' characteristics and the prevalence of psychiatric and non-psychiatric comorbidity in a local inpatient rehabilitation service, as well as to investigate the impact of the whole-system approach to rehabilitation on future utilization of mental health services and to analyze the cost-effectiveness and quality of this service. Method Patients managed over 3 years in a psychiatric rehabilitation inpatient unit were self-controlled; they were retrospectively (pre-rehabilitation) and prospectively (post-rehabilitation) examined for readmission rate, length of stay (LOS), and emergency room (ER) visits. Relevant information was retrieved from Discharge Abstract Database (DAD), Patient Registration System (STAR), and Emergency Department Information System (EDIS). The quality of care in the rehabilitation unit was examined using the Quality Indicator for Rehabilitative Care (QuIRC), and the cost analysis was conducted using data obtained from a single-payer government medical service insurance (MSI) billing system. Results Of the 185 patients admitted over the study period, 158 were discharged. There was a significant reduction in readmission rate (64% decrease), LOS (6,585 fewer days spent in hospital), and ER presentations (166 fewer visits) (P < 0.0001), respectively. There were substantial subsequent cost savings in the post-rehabilitation year. Conclusion and implications for practice In the 3-year study, an inpatient psychiatric rehabilitation service in Nova Scotia, Canada, resulted in the successful discharge of most patients with severe and persistent mental illness to more socially inclusive environments. It also reduced their post-rehabilitation mental health service utilization, hence greatly enhancing the effectiveness and efficiency of these services.